KETAHANAN KAYU RANDU (Ceiba pentandra L.) DAN KAYU KEMIRI (Aleurites molucana Willd) YANG DIAWETKAN DENGAN DAUN KIRINYUH (Choromolaena odorata) TERHADAP SERANGAN RAYAP TANAH (Macrotermes gilvus) - Rahmad Isnandar; Diana Ulfah; Lusyiani Lusyiani (Universitas Lambung Mangkurat, 2020)
This study aims to measure absorption, retention, percentage of weight loss, degree of purity of the types of wood and candlenut wood, and identify the type of termites that attack the wood. The research data were analyzed using factorial Completely Randomized Design (CRD) with 2 factors (factor A) type of wood and (factor B) preservative concentration with 10 replications, to get the effectiveness of using the leaves preservative ingredients on candlenut wood and lumber wood using the cold soaking method. This research was conducted for 3 months in the Laboratory and Arboretum of the Faculty of Forestry, Lambung Mangkurat University, Banjarbaru. The results of this study indicate that the use of preservatives with a concentration of 100 grams, 200 grams, 300 grams and controls is ineffective because the results of the test data are not significant.Keywords: Randu; Kemiri; Kirinyuh; Preservation; Termite